Teaching of transferable teamwork competencies in higher education: development of the TWC Training Protocol© - Campbell, Cynthia G.; Babik, Iryna; Crowley, Stephen J. (Frontiers in Education, 2025)
Teamwork competencies are essential for career success, yet higher education often lacks structured, effective training for developing those. This paper introduces the Teamwork Competency (TWC) Training Protocol©, a structured framework grounded in action research principles, designed to enhance students’ teamwork competencies through iterative cycles of planning, action, reflection, and adjustment. It integrates theoretical foundations of teamwork with experiential learning, incorporating team charters, self-and peer assessments, and guided team reflections. Theoretical foundations and protocol development are described, followed by a pilot study across disciplines in Malaysia and the United States. Results suggest that the protocol advances key student teamwork competencies, such as open communication, planning and coordinating, goal setting, collaborative problem-solving, performance monitoring, as well as building trust and team cohesion. It also mitigates common challenges of social loafing and interpersonal conflict. Thus, the introduced protocol provides a scalable, evidence-based approach to teaching teamwork in higher education.